Causes of treatment failure in patients with endometrial cancer treated with postoperative radiotherapy - Spych, Michał; Gottwald, Leszek; Jesień-Lewandowicz, Emilia; Chałubińska, Justyna; Sobotkowski, Janusz; Fijuth, Jacek (Menopause Review/Przegląd Menopauzalny, 2010)
Introduction: The treatment of choice for patients with early clinical stage uterine cancer is surgical inter- vention. In complementary treatment in standard use is radiotherapy (teletherapy and brachytherapy). In case of onset of disease recurrence, salvage treatment frequently proves ineffective, which is connected with a high percent of deaths in this group of patients. The aim was to evaluate the causes of treatment failure in patients with endometrial cancer treated with postoperative radiotherapy. Material and methods: Twenty-eight patients aged between 49 and 84 years were enrolled in the study, in whom for the period from 2002 until 2004 postoperative radiotherapy was applied, and in whom during the period of five years after treatment termination disease recurrence was observed. Results: In the analyzed group of patients the 2- and 4-year disease-free survival (DFS) was 41% and 11% respectively. The 2- and 5-year overall survival (OS) was 67% and 13%. Locoregional failures occurred in 5 (17.7%) patients. Distant metastases were detected in 15 (63.6%) patients. In 8 (28.6%) patients, distant metastases occurred simultaneously with local relapse. Neither of the treatment methods after disease recurrence significantly extended the survival of patients (p = 0.82). Patients’ age was the sole prognostic factor which has a statistically significant impact on DFS. On the other hand an adverse affect on overall survival was demonstrated for the variable of the time of disease recurrence. In the group of patients in whom the recurrence was demonstrated earlier than 6 months after treatment termination the OS was significantly shorter (p = 0.001). Conclusions: Distant metastases are the main cause of failures of patients’ treatment for endometrioid endometrial cancer. Neither of the treatment methods after disease recurrence significantly extended the survival of patients. Shorter time to disease recurrence is a negative prognostic factor with reference to overall survival.